Comparación de esquemas de tratamiento inmunosupresor en trasplante renal de donante vivo, en el Hospital Edgardo Rebagliati Martins, 2015 - Quiroz Rodriguez, Diego Armando (2019)
The aim of the present report was to compare the immunosuppressive regimens in living donor kidney transplantation from 3 countries, with the one that was in exercise at the National Hospital Edgardo Rebagliati Martins (HNERM) in 2015. To do this, a search for information was carried out through the Pubmed database, where the published evidence was analyzed. The immunosuppressive treatments presented by the Clinical Practice Guidelines of: Spain, Chile and Mexico were used, in comparison with the HNERM, 2015. The same division of schemes was observed in the Clinical Practice Guidelines: induction treatment and maintenance of the transplant, except in the standard donor-recipient classification, and ABO-incompatible. It was concluded that the scheme of immunosuppressive treatment in kidney transplantation from living donor of the HNERM 2015, is similar to the Clinical Practice Guide of Spain in all the tables of the classification, except in standard donor-recipient, where it resembles to the Clinical Guide of Chile